The relationship between motivation on working environment and job satisfaction among support staff at Public Sector / Alya Dayana Roslan ... [et al.] - Roslan, Alya Dayana; Mohamad Welman, Hamizah; Majidi, Nur Fatihah Ajmal; Ibrahim, Nurdiana (2018)
Today, the implementation of job satisfaction is important for most organizations either public or private. Another term for job satisfaction as defined by Armstrong (2006) is the attitude and feeling's that by coming to work early, not delaying their task and enjoying their job. Positive and favourable attitudes towards the job indicate job satisfaction. The study conduct by Spector (1997) lists three important features of job satisfaction. First, organizational should be guided by human values. Such organizational will be oriented towards treating the workers fairly and with respect. In such cases, the assessment of job satisfaction may serve as a good indicator of employee effectiveness. High levels of job satisfaction may be signs of a good emotional and mental state of employees. Second, the behaviours of workers depend on their level of job satisfaction which will affect the function and activities of the organizations business.